Restauración ecológica con plantas nativas para la conservación de suelos erosionados en el Campus Salache de la Universidad Técnica de Cotopaxi. - Broncano Toaquiza, José Fernando (2023)
The objective of this research was to evaluate the ecological restoration with native plants for the conservation of eroded soils in the Salache Campus of the Technical University of Cotopaxi. The species were alder (Alnus glutinosa), mallow (Malva sylvestris), linden (Sambucus nigra). , retamo-liso (Genista monspessulana) with the incorporation of organic fertilizers, nutriabono, ecofertiplus, fertiplus, a (DBCA) was applied, with 16 treatments and 3 repetitions, with Tukey tests at 5% for the indicators that had statistical significance, It was evaluated at 30, 60, 90 and 120 days respectively: in percentage of yield the best range was broom + ecofertilizer and mallow + fertiplus with 100%, plant height broom + nutriabono with 36, 51, 55, 61 cm and broom + ecofertilizer with 34.51, 53 and 59 cm., stem diameter (nutriafer) with 4.28; 5.67; 6.42 and 6.92 mm., number of branches (ecofertilizer) with 10.17; 16.5; 20.14 and 26.5 units, number of leaves (broom) with 7.42; 9.42; 10.92 and 12.92 units, weight of the soil (linden) with 10.84; 11.26; 11.48 and 11.63 kg. , root length (nutriacompost) with 16.25; 29.25; 30.83 and 34.25 cm., number of secondary roots (linden) with 15.13; 22,31; 23.63 and 25.63 units, root volume (alder) with 2.04; 2.08; 2.75 and 5.25 ml., root weight (ecofertilizer) with 6.28; 8.83; 9.5 and 10.42 gr., soil pH at the beginning 8.32; at the end 6.35 (linden + control), organic matter at the beginning 2.21%; at the end 3.21% (alder + control), primary macronutrients there were increases (N) from 0.13 to 0.16, (P) from 76.1 to 94 ppm; (K) from 94 to 98 ppm, micronutrients (Ca) from 2.6 to 4.4 ppm, (Mg) from 11.9 to 14.9. The species that has responded best is the broom and ecobanaza since the favorable plant and soil response was observed.